Neurochemical profile of the human cervical spinal cord determined by MRS. (31st August 2016) - Hock, Andreas; Wilm, Bertram; Zandomeneghi, Giorgia; Ampanozi, Garyfalia; Franckenberg, Sabine; Zoelch, Niklaus; Wyss, Patrik Oliver; De Zanche, Nicola; Nordmeyer‐Maßner, Jurek; Kraemer, Thomas; Thali, Michael; Ernst, Matthias; et al.
Abstract : MRS enables insight into the chemical composition of central nervous system tissue. However, technical challenges degrade the data quality when applied to the human spinal cord. Therefore, to date detection of only the most prominent metabolite resonances has been reported in the healthy human spinal cord. The aim of this investigation is to provide an extended metabolic profile including neurotransmitters and antioxidants in addition to metabolites involved in the energy and membrane metabolism of the human cervical spinal cord in vivo. To achieve this, data quality was improved by using a custom‐made, cervical detector array together with constructive averaging of a high number of echo signals, which is enabled by the metabolite cycling technique at 3T. In addition, the improved spinal cord spectra were extensively cross‐validated, in vivo, post‐mortem in situ and ex vivo . Reliable identification of up to nine metabolites was achieved in group analyses for the first time. Distinct features of the spinal cord neurochemical profile, in comparison with the brain neurotransmission system, include decreased concentrations of the sum of glutamate and glutamate and increased concentrations of aspartate, γ‐amino‐butyric acid, scyllo‐inositol and the sum of myo‐inositol and glycine. Abstract : Magnetic resonance spectroscopy enables insight into the chemical composition of central nervous system tissue. However, technical challenges degrade the data quality when applied to the human spinal cord. By introducing an innovative acquisition and post‐processing strategy we were able to improve data quality, allowing us to obtain insight into the neurotransmission and antioxidant systems of the human spinal cord for the first time. In addition, the improved spinal cord spectra were extensively cross‐validated with spinal cord and brain measurements in vivo, in situ and ex vivo .